Potensi dan Rencana Strategis Pengembangan Ekowisata Berkelanjutan di Kawasan Danau Sentani, Kabupaten Jayapura, Provinsi Papua (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
Lake Sentani is an important ecosystem icon in Papua Province and plays a role in supporting social, economic, and ecological activities for the local community. Based on the Jayapura Regency Spatial Plan (RTRW) 2008-2028, Lake Sentani is categorized as a leading tourist attraction and main destination in Jayapura. This lake has great ecotourism potential, not only because of its natural charm, but also because of the aesthetic value of the historical heritage and the diversity of fauna found in the area. Ecotourism development can support conservation efforts while providing a significant direct economic impact on the local community, by considering three important aspects in its management, namely ecological, economic, and resource aspects. Sustainable ecotourism development in Lake Sentani will affect the interaction between the local community and the tourist area. This research was conducted in the Lake Sentani tourist destination area, Jayapura Regency, from April to May 2025. Data were obtained by conducting direct observations in the field, collecting documentation, distributing questionnaires, and conducting interviews to collect information about nature-based tourist attractions, supporting facilities, as well as community views and visitor interests. The data obtained were then analyzed using the SWOT approach to develop a strategic plan to advance ecotourism in the Lake Sentani area. Findings from the analysis indicate that the most appropriate strategy to implement is the SO (strengths and opportunities) strategy, on the grounds that the available ecotourism resources have great opportunities but have not been fully optimized.